Imaging in Whiplash-Associated Disorders - Schollaert, Joris; Van Goethem, Johan W.M. (Seminars in Musculoskeletal Radiology, 2023)
“Whiplash,” a term describing the severe acceleration and deceleration forces applied to the head, craniocervical junction (CCJ), and cervical spine during trauma, is one of the most frequent mechanisms of injury to the CCJ. The CCJ is a complex region at the transition of the cranium and the cervical spine, essential for maintaining craniocervical stability. In whiplash injuries, the CCJ may be compromised due to underlying ligamentous or, less frequently, osseous, intravertebral disk and/or muscular lesions. Imaging is crucial in detecting acute lesions but may also play a role in the follow-up of chronic pathology because soft tissue lesions and progressive disk pathology could contribute to a whiplash-associated disorder.
Keywords: cervical spine; craniocervical junction; magnetic resonance imaging; computed tomography; whiplash injuries